How to Generate Synthetic Paintings to Improve Art Style Classification - Pérez, Sarah Pires; Cozman, Fabio Gagliardi (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2021: Anais da X Brazilian Conference on Intelligent Systems, 2021)
Indexing artwork is not only a tedious job; it is an impossible task to complete manually given the amount of online art. In any case, the automatic classification of art styles is also a challenge due to the relative lack of labeled data and the complexity of the subject matter. This complexity means that common data augmentation techniques may not generate useful data; in fact, they may degrade performance in practice. In this paper, we use Generative Adversarial Networks for data augmentation so as to improve the accuracy of an art style classifier, showing that we can improve performance of EfficientNet B0, a state of art classifier. To achieve this result, we introduce Class-by-Class Performance Analysis; we also present a modified version of the SAGAN training configuration that allows better control against mode collapse and vanishing gradient in the context of artwork.